Apoyo Social en Cuidadores Informales de Pacientes con Demencia (2022)
This research work aims to analyze the characteristics of social support in informal caregivers of patients with dementia in Cundinamarca, Colombia, in addition to determining each of the dimensions of social support and how these can influence the wellbeing of the informal caregiver, also this study aimed to evaluate the consequences of the extensive and complex job that these patients require from the caregiver. This research was developed with a descriptive quantitative methodology, which allows knowing and describing the characteristics of social support present in caregivers.